Analyzing if calcium channel blockers can save pregnant patients with persistent hypertension from developing preeclampsia: Menganalisis apakah penghambat saluran kalsium dapat menyelamatkan pasien hamil dengan hipertensi persisten dari pengembangan preeklampsia - Nada Mohammed Basil; Shatha Salim Mahmood; Ola Hikmat Makki (Universitas Muhammadiyah Sidoarjo, 2024)
Pregnant women with chronic hypertension face elevated risks during pregnancy, necessitating effective management strategies. This study evaluates the potential benefits of combining low-dose aspirin therapy with calcium channel blockers, particularly nifedipine, in this population. Thirty-seven participants were enrolled between July 2015 and September 2017, receiving combination therapy as part of their treatment regimen. Results indicate effective blood pressure control without significant adverse events, with 36.8% experiencing preeclampsia but no severe cases reported. Neonatal outcomes were generally favorable, although 15% of babies were classified as small-for-gestational-age, all achieving Apgar scores between nine and ten. These findings suggest promising outcomes with combination therapy, emphasizing the need for further research to optimize management approaches for pregnant individuals with chronic hypertension. Highlight: Controlled blood pressure: Combination therapy effectively manages blood pressure in chronic hypertension. Lowered severe complications: Potential reduction in eclampsia and placental abruption risks. Positive neonatal outcomes: Favorable Apgar scores and reduced small-for-gestational-age incidence. Keywoard: Chronic Hypertension, Pregnancy, Combination Therapy, Low-Dose Aspirin, Calcium Channel Blockers